Rapid visual characterization of alkaloid changes in traditional processing of Tibetan medicine Aconitum pendulum by high-performance thin-layer chromatography coupled with desorption electrospray ionization mass spectrometry imaging - Tan, Xiaoyan; He, Qingxiu; Pei, Zhaoqing; Liu, Yue; Feng, Zige; Li, Congying; Tang, Ce; Zhang, Yi (Frontiers in Pharmacology, 2023)
Radix Aconiti, also known as Tie-bang-chui (TBC), Pang-a-na-bao, and Bang-na, is a typical aconitum Tibetan medicine and a perennial herb of the genus Aconitum pendulum Busch. and A. flavum Hand. -Mazz. dry roots. It has high toxicity and remarkable efficacy; as such, it is a typical “highly toxic and effective” drug that needs be processed and used. Processing methods of this Tibetan medicine include non-heating of highland barley wine (HBW) and fructus chebulae soup (FCS). In this study, high-performance thin-layer chromatography (HPTLC) and desorption electrospray ionization mass spectrometry imaging (DESI-MSI) were used to analyze the chemical composition of TBC processed by FCS (F-TBC) and HBW(H-TBC). This work aimed to understand differences in chemical composition between non-heat processed products and raw TBC. A total of 52 chemical constituents were identified in raw and processed products, and the chemical composition of F-TBC and H-TBC changed slightly compared with that of raw TBC. The processing mechanism of H-TBC was also different from that of F-TBC, which might be related to the large amount of acidic tannins in FCS. The combination of HPTLC and DESI-MSI could be an effective method for rapid identification of chemical components and changing rules in ethnic medicine. The wide application of this technology provides not only an alternative method for the traditional separation and identification of secondary metabolism but also a reference for research on the processing mechanism and quality control of ethnic medicine.